Characterization of regional earth magnetic activity based on MAGDAS data / Khairul Afifi Nasuddin and Muhammad Adib Haron - Nasuddin, Khairul Afifi; Haron, Muhammad Adib
Earth magnetic data can be measured by magnetometer. Magnetic Data Acquisition System and other devices. MAGDAS is a realtime system magnetometers that are being deployed by Kyushu Sangyo University of Fukuoka, Japan. The earth magnetic data from the MAGDAS can be used as part of earth magnetic data monitoring, mainly for earth events such as earthquake and space events such as geomagnetic storm. For this project, data from stations at the north, equatorial and south region are considered as monitored data to be analyzed. The analyses are based on the different biases of MAGDAS data at different region. From the analysis, the earth magnetic polar at different region can be mapped and defined. The results are useful to give the regional of magnetic format data.